Rotor losses in fault-tolerant permanent magnet synchronous machines - Raminosoa, Tsarafidy; Gerada, Christopher; Othman, Md Nazri; De Lillo, Liliana (The Institution of Engineering and Technology, 2011)
The necessary reliability of safety-critical aerospace drive systems is often partly achieved by using fault-tolerant (FT) electrical machines. There are numerous published literatures on the design of FT machines as well as on control algorithms used to maintain drive operation with an incurred fault. This study is set to look at the rotor losses in three- and five-phase surface mount permanent magnet machines when operating in faulty mode in order to highlight the influence of the post-fault control strategy and winding configuration. Although the work presented in this study is mainly focused on FT control methodologies targeted at mitigating phase open circuit faults, the implications of short-circuit faults is also considered and discussed.